The Relationship Between Husband Support and Pregnant Women's Interest in The Use of Postpartum Contraceptives at The Kaliori Health Center, Rembang Regency - Umi Arimbi Afi Apriliony; Noor Hidayah; Rusnoto Rusnoto (Advances in Healthcare Research, 2026)
Purpose: This study aimed to determine the relationship between husband support and pregnant women’s interest in using postpartum contraceptives at Kaliori Health Center, Rembang Regency. It was hypothesized that positive husband support would be associated with higher maternal interest in postpartum contraceptive use. Research Method: This study used a quantitative analytical design with a cross-sectional approach. Data were collected from pregnant women at Kaliori Health Center using questionnaires and analyzed through univariate and bivariate methods. The bivariate analysis was performed to identify the relationship between husband support and maternal interest in postpartum contraception. Results and Discussion: The results showed that 66 respondents (55.0%) received positive support from their husbands, while 54 respondents (45.0%) received negative support. Positive interest in postpartum contraceptive use was reported by 61 respondents (50.8%), while 59 (49.2%) had negative interest. Most pregnant women who received positive husband support also showed positive interest in postpartum contraception. Statistical analysis showed a significant relationship between husband support and maternal interest (p = 0.000; p < 0.05). Implications: These findings indicate that husband involvement plays an important role in encouraging maternal readiness to use postpartum contraception. Strengthening couple-based counseling and reproductive health education is recommended to improve postpartum family planning participation.